Conflict between ambitions and real life of the hero in the novel” The Moon and Sixpence” by Somerset Maugham - Isamova Dilfuza Rakhmatovna (Genius Publishing Group, 2022)
This article aims to analyze the adventurous life and bitter destiny of the main character of “The Moon and Sixpence”. The work reveals the complexity of the human nature and represent struggles in which a choice has to be made between reality and ideality. Clearly ,the hero Strickland being a painter, faces a real hesitation between selecting his family or choosing his dream of painting . However , his dream becomes untouchable, and he is not able to find out the real meaning of art.
Keywords: Adventurous life; complexity; reality; ideality